Pelatihan Pendidikan Kognitif Anak Dengan Aplikasi Open Smart Rigester Platform - Sudirman (DEDIKASI : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service reported the process on training of cognitive development using a mobile application for real-time data management information system in early childhood education, it can help tracking child education and assist teacher in monitoring and evaluation on child services. A community service was carried out to gather necessary information through a training directly entry in the field using mobile development, application testing and analysis that was conducted on for 50 children. To obtain a full picture on early childhood education, data on childhood education shall be mapped and linked in one application. We introduce a mobile app to systematically compile the individual as well as group data across different aspects of child life, ranging from early child education. Using a tablet PC or mobile phone, data could be easily entered at anytime by the person. Due to still poor infrastructure at the grass root level, the system also allows a safety store offline that could automatically link to server when network connection is available. The immediate data entry will provide real-time data report that could be accessed by any relevant stakeholders at any levels to response accordingly. However, to avoid misuse of data, the access will also be restricted with a secured login system. Based on the community service, this application is easily applicable for the training of real-time monitoring and evaluation on early childhood education.